2017
DOI: 10.3389/fphar.2017.00367
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Toxicity Associated with Tyrosine Kinase Inhibitors: Mitochondrial Damage and Inhibition of Glycolysis

Abstract: Tyrosine kinase inhibitors (TKIs) are anticancer drugs with a lesser toxicity than classical chemotherapeutic agents but still with a narrow therapeutic window. While hepatotoxicity is known for most TKIs, underlying mechanisms remain mostly unclear. We therefore aimed at investigating mechanisms of hepatotoxicity for imatinib, sunitinib, lapatinib and erlotinib in vitro. We treated HepG2 cells, HepaRG cells and mouse liver mitochondria with TKIs (concentrations 1–100 μM) for different periods of time and asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
75
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 53 publications
11
75
1
Order By: Relevance
“…Moreover, cellular depletion of GSH increased cytotoxicity . These results concur with those of Paech et al using rifampicin in HepaRG cells and those of Teo et al, who reported an increased hepatotoxicity upon dexamethasone treatment both in vitro and in vivo. Eno et al studied the comparative effects of lapatinib 30 and O ‐dealkylated lapatinib 31 on HepG2 cells.…”
Section: Tki Hepatotoxicity: Evidence Of Rm Involvementsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, cellular depletion of GSH increased cytotoxicity . These results concur with those of Paech et al using rifampicin in HepaRG cells and those of Teo et al, who reported an increased hepatotoxicity upon dexamethasone treatment both in vitro and in vivo. Eno et al studied the comparative effects of lapatinib 30 and O ‐dealkylated lapatinib 31 on HepG2 cells.…”
Section: Tki Hepatotoxicity: Evidence Of Rm Involvementsupporting
confidence: 90%
“…However, as far as TKI are concerned, very few data support the role of RM rather than the parent drug in TKI‐induced hepatotoxicity; these cases are discussed in this section. However, reporting the current state of knowledge of the entire spectrum of toxicity mechanisms at a cellular level is beyond the scope of this review …”
Section: Tki Hepatotoxicity: Evidence Of Rm Involvementmentioning
confidence: 99%
“…1416,54,55 Paech et al recently reported an investigation on the mechanisms of hepatocellular toxicity of sunitinib and other tyrosine kinase inhibitors (imatinib, erlotinib, and lapatinib) in HepG2 and HepaRG cells. 56 Treatment of HepG2 cells with sunitinib was shown to increase the production of reactive oxygen species, disrupt the mitochondrial membrane potential, deplete glutathione content, and induce apoptosis in a concentration-dependent manner. 56 In the metabolically competent cell line Hep-aRG, 57,58 the cytotoxic effects of sunitinib increased following induction by rifampin, compared with sunitinib treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…56 Treatment of HepG2 cells with sunitinib was shown to increase the production of reactive oxygen species, disrupt the mitochondrial membrane potential, deplete glutathione content, and induce apoptosis in a concentration-dependent manner. 56 In the metabolically competent cell line Hep-aRG, 57,58 the cytotoxic effects of sunitinib increased following induction by rifampin, compared with sunitinib treatment alone. 56 This finding suggests that formation of toxic metabolite(s) may be involved in sunitinib-induced hepatotoxicity, but the parent drug itself may also be involved in mediating some of the hepatotoxic effects associated with sunitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Paech et al, examined the toxic effects of four tyrosine kinase inhibitors (imatinib, sunitinib, lapatinib, and erlotinib) in HepG2 cells, HepaRG cells, and isolated mouse liver mitochondria [65]. In HepG2 cells, cytotoxicity, as characterized by the release of adenylate kinase, was shown for sunitinib at 5–10 µM, and for lapatinib at 10–20 µM, after 24–48 h of incubation.…”
Section: Downstream Toxicity Mechanisms Of Tyrosine Kinase Inhibitorsmentioning
confidence: 99%